2019
DOI: 10.1002/smll.201805475
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Mn3O4 Nanocages with High‐Efficiency Charge Transfer for Enhancing Electro‐Optic Properties of Liquid Crystals

Abstract: Improving electro‐optic properties is essential for fabricating high‐quality liquid crystal displays. Herein, by doping amorphous Mn3O4 octahedral nanocages (a‐Mn3O4 ONCs) into a nematic liquid crystal (NLC) matrix E7, outstanding electro‐optic properties of the blend are successfully obtained. At a doping concentration of 0.03 wt%, the maximum decreases of threshold voltage (Vth) and saturation voltage (Vsat) are 34% and 31%, respectively, and the increase of contrast (Con) is 160%. This remarkable electro‐op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…The measurement results (Figure 2h,i) show that the nanoclusters contain two interlayer spacings of 0.223 and 0.248 nm, corresponding to the MnO(200) and Mn 3 O 4 (211) crystal planes, respectively. 35,36 This fact confirms the coexistence of MnO and Mn 3 O 4 in MnO x @C-R and echoes the conclusion of XRD characterization. Although the macroscopic distribution of MnO x @C is similar to that of MnO x @C-R, the nanoclusters in MnO x @C are almost all Mn 3 O 4 , which reveals the fact that Mn 3 O 4 is dominant in MnO x @C (shown in Figure S7d).…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…The measurement results (Figure 2h,i) show that the nanoclusters contain two interlayer spacings of 0.223 and 0.248 nm, corresponding to the MnO(200) and Mn 3 O 4 (211) crystal planes, respectively. 35,36 This fact confirms the coexistence of MnO and Mn 3 O 4 in MnO x @C-R and echoes the conclusion of XRD characterization. Although the macroscopic distribution of MnO x @C is similar to that of MnO x @C-R, the nanoclusters in MnO x @C are almost all Mn 3 O 4 , which reveals the fact that Mn 3 O 4 is dominant in MnO x @C (shown in Figure S7d).…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…38−41 We calcined the amorphous metal hydroxide nanocages to obtain corresponding amorphous metal oxide nanocages. 42,43 By further optimizing the reaction conditions, we prepared binary amorphous nanocages (Ni−Zn hydr(oxy)oxide, Ni−Co hydr(oxy)oxide), etc.) 44,45 and ternary metal hydroxide (Cu−Ni−Fe hydr(oxy)oxide, etc.)…”
Section: Three-dimensional Amorphous Nanomaterialsmentioning
confidence: 99%
“…the reasonable enhancement mechanisms are highlighted. 18,[41][42][43]55,56 We used amorphous ZnO nanocages as a SERS substrate and observed a SERS enhancement factor (EF) as high as 6.62 × 10. 5,42 X-ray absorption near-edge structure (XANES) characterization and first-principles density functional theory (DFT) calculations showed that the amorphous structure with a low coordination number and the abundant oxygen defects in the ZnO nanocages had a higher electronic density of states and a narrower energy gap, resulting in a higher SERS activity than the corresponding crystalline compound.…”
Section: Electrocatalytic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations